Metode Qira’ati Menggunakan media Audiovisual dalam Peningkatan Pembelajaran Membaca Al-Qur’an Sesuai Kitab Tuhfatul Athfal pada Peserta Didik MTs Al-Falakiyah Bogor Barat - Rahmatunnisa, Salma; Yunizul Pesha, Indry Nirma; Sidqy, Mukhrij (Ikatan Da'i Indonesia, 2025)
The Qur'an is the main guideline for Muslims, which must be studied and practiced. The phenomenon at MTs Al-Falakiyah Bogor Barat shows that most students still have difficulty reading the Qur'an, especially in terms of fluency, smoothness, and accuracy of tajwid. This study focuses on the implementation of the Qira'ati method based on audiovisual media in the eighth grade, the improvement of reading skills after the application of this method, as well as the supporting and inhibiting factors of learning. This study uses a qualitative descriptive analysis approach with techniques of interviews, observation, documentation, and Qur'an reading tests. The results of the study show that the implementation of the Qira'ati method was carried out through the stages of planning, implementation, and evaluation, with teachers as facilitators and the support of homeroom teachers, resulting in a significant improvement in Quran reading skills. Of the 52 students (18 from class VIII D and 20 from class VIII E), 38 students showed significant improvement in fluency, smoothness, and application of tajwid, while 14 students (8 from class VIII D and 6 from class VIII E) were still hampered by low motivation to learn, lack of confidence, and differences in learning focus. Supporting factors included audiovisual facilities, guidebooks, a conducive learning environment, and support from teachers and peers, while inhibiting factors stemmed from within the students themselves and limited learning time. Thus, the audiovisual-based Qira'ati method effectively improved Quran reading skills, with recommendations for strengthening motivation and intensive assistance for students who still experienced difficulties.